PEMANFAATAN LIMBAH BATU GRANIT SEBAGAI CAMPURAN AGREGAT PADA AC-L - Ahmad Ridwan; Yosef Cahyo Setianto Poernomo (Litbang Pemas - Universitas Islam Lamongan, 2018)
Granite waste is generated at the time of processing the granite rock that is not utilized, it can be also a rest – the rest of the project. Utilization of waste material roughness to granite road is one way to reduce the waste of the granite. This research aims to know the benefits of waste granite coarse aggregate as substitute against marshall on the mix characteristic laston or AC-b. ingredients used include: Semen Gresik brand Filler, sand purchased from stores building in Kediri, Grey stone which in may from Winongsari Grogol, corals that are purchased from shops in Kediri, Asphalt comes from Pertamina, granite Waste obtained from the project. Mix laston or AC-L with granite rock waste as a substitute for coarse aggregate using a variation of 10%, 20%, and 30%. The results of this research it is known that the use of granite waste can enhance the characteristics of Marshall. Mix the waste with best laston granite aggregate as substitute coarse waste levels obtained at 20%, with the following results: Marshall Stability 1050.67 kg, Melting/4.00 mm Flow, Marshall Quotient 262.67 mm.